Reconciling conflicting phylogenies in the origin of sweet potato and dispersal to Polynesia - Muñoz Rodríguez, P.; Carruthers, T.; Wood, J.R.I.; Williams, B.R.M.; Weitemier, K.; Kronmiller, B.; Ellis, David; Anglin, Noelle L.; Longway, L.; Harris, S.A.; Rausher, M.D.; Kelly, S.; et al. (Elsevier, 2018)
The sweet potato is one of the world’s most widely consumed crops, yet its evolutionary history is poorly understood. In this paper, we present a comprehensive phylogenetic study of all species closely related to the sweet potato and address several questions pertaining to the sweet potato that remained unanswered. Our research combined genome skimming and target DNA capture to sequence whole chloroplasts and 605 single-copy nuclear regions from 199 specimens representing the sweet potato and all of its crop wild relatives (CWRs). We present strongly supported nuclear and chloroplast phylogenies demonstrating that the sweet potato had an autopolyploid origin and that Ipomoea trifida is its closest relative, confirming that no other extant species were involved in its origin. Phylogenetic analysis of nuclear and chloroplast genomes shows conflicting topologies regarding the monophyly of the sweet potato. The process of chloroplast capture explains these conflicting patterns, showing that I. trifida had a dual role in the origin of the sweet potato, first as its progenitor and second as the species with which the sweet potato introgressed so one of its lineages could capture an I. trifida chloroplast. In addition, we provide evidence that the sweet potato was present in Polynesia in pre-human times. This, together with several other examples of long-distance dispersal in Ipomoea, negates the need to invoke ancient human-mediated transport as an explanation for its presence in Polynesia. These results have important implications for understanding the origin and evolution of a major global food crop and question the existence of pre-Columbian contacts between Polynesia and the American continent.